THE IMPACT OF FRAMED STORYTELLING ON PUBLIC PERCEPTION AND SOCIAL MOVEMENTS - Тіманков, Ігор (SWorldJournal, 2025)
The article analyzes the impact of framed storytelling on public perception and social movements, particularly its role in shaping public opinion and mobilizing social groups. The study aims to explore the mechanisms through which framed storytelling infl